Network-Based Transformer Models – A Transient Analysis - Sauseng, Alexander; Reinbacher-Kostinger, Alice; Hamberger, Peter; Kaltenbacher, Manfred; Roppert, Klaus (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
This contribution is about network-based transformer models. Two models (single- and three-phase) are derived, whereas Hopkinson’s analogy is used to depict the magnetic domain. Therein, an energy-based hysteresis model is incorporated to represent the magnetic core. The solution strategy is a second-order variable step size backward differentiation formula (BDF2) in time domain, yielding the transient response of the two transformers. Finally, the simulation results are compared to measurements.